Application of Component Mode Synthesis to Protein Structure for Dynamic Analysis - Kim, Jae In; Eom, Kilho; Kwak, Moon Kyu; Na, Sungsoo (TECH SCIENCE PRESS, 2008)
This paper concerns the application of component mode synthesis for biomolecule modeling to understand protein dynamics. As for protein dynamics, eigenvalue problem should be formulated to obtain eigenvalue, eigenvector and thermal fluctuation. To describe the thermal fluctuation of protein, normal mode analysis is introduced and normal modes identify the dynamic behavior of protein very well. Component mode synthesis considers the given complex structure as ail assembly of smaller components. The selection of a component may be arbitrary. When the component mode synthesis is applied to formulate the eigenvalue problem of protein structure, we selected a protein which may be composed of two and/or four domains. The domain of protein can be considered as it component. In this sense the number of component is increased as necessary, and the size of each component is decreased for fast calculation. The component mode synthesis widely used in engineering was well applied to understand protein dynamics in present Study.